The Evaluation of 3D Printing Resins for Permanent Full Coverage Restorations - Tran, QUOC KIET. (Tufts University. Tisch Library., 2025)
Thesis (M.S.)--Tufts University, 2025.; Submitted to the Dept. of Posthodontics.; Advisor: Yo-Wei Chen.; Committee: Matthew D. Finkelman, Yukio Kudara, Mariam Margvelashvili-Malament, and Konstantinos Vazouras.; Keyword: Dentistry.